2002
DOI: 10.1002/ajh.10056
|View full text |Cite
|
Sign up to set email alerts
|

Effective hemostasis with rFVIIa treatment in two patients with severe thrombocytopenia and life‐threatening hemorrhage

Abstract: We report two patients with severe thrombocytopenia and life-threatening bleeding that were successfully managed with recombinant activated factor VII (rFVIIa). The ®rst was a 75-year-old male with Waldenstro È mÕs macroglobulinemia. During a therapeutic course with¯udarabine, he developed severe autoimmune thrombocytopenia resistant to conventional treatment, followed by persistent uncontrollable nasal bleeding. Platelet transfusions failed to increase the platelet count and control the hemorrhage. When hemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 19 publications
2
52
0
2
Order By: Relevance
“…Response to rVIIa was predicted by two factors: the delay between the onset of bleeding and treatment and the severity of bleeding. These results are less promising than those published by the 'International Registry on Recombinant Factor VIIa and Congenital Platelet Disorders' (Poon et al, 2001) and a number of other small series and patient reports (Chuansumrit et al, 1999;d'Orion et al, 2000;Gerotziafas et al, 2002). Reasons for this difference in clinical efficacy are not clear; one possible contributing factor is that our cohort consisted exclusively of children, who may differ from adults in the speed of presentation and overall response to treatment.…”
Section: Rviia In Children With Platelet Function Disordersmentioning
confidence: 71%
See 1 more Smart Citation
“…Response to rVIIa was predicted by two factors: the delay between the onset of bleeding and treatment and the severity of bleeding. These results are less promising than those published by the 'International Registry on Recombinant Factor VIIa and Congenital Platelet Disorders' (Poon et al, 2001) and a number of other small series and patient reports (Chuansumrit et al, 1999;d'Orion et al, 2000;Gerotziafas et al, 2002). Reasons for this difference in clinical efficacy are not clear; one possible contributing factor is that our cohort consisted exclusively of children, who may differ from adults in the speed of presentation and overall response to treatment.…”
Section: Rviia In Children With Platelet Function Disordersmentioning
confidence: 71%
“…Recent patient reports have suggested that recombinant factor VIIa (rVIIa) (NovoSeven Ò ; Novo Nordisk, Hillerød, Denmark) may be effective therapy for treatment of bleeding in patients with congenital platelet function defects and other acquired platelet disorders, including thrombocytopenia (Tengborn & Petruson, 1996;Peters & Heijboer, 1998;Ancliff et al, 1999;Chuansumrit et al, 1999;Poon et al, 1999Poon et al, , 2001d'Orion et al, 2000;Poon & d'Orion, 2000;Vidarsson & Onundarson 2000;Gerotziafas et al, 2002). The exact mechanism of how rVIIa improves haemostasis in platelet disorders is not fully understood but it is proposed that the increase in thrombin generated on the platelet surface as a result of direct activation of factors IX and X by rVIIa may result in faster platelet activation via this mechanism, compensating for either a lower number of platelets present or dysfunctional platelets (Monroe et al, 1997(Monroe et al, , 2002Kjalke et al, 2001).…”
mentioning
confidence: 99%
“…To this end, FVIIa analogs with increased intrinsic activity have been generated that exhibit superior hemostatic profiles in vitro. [6][7][8] These analogs may also be used as more efficacious hemostatic agents in other indications where efficacy of rFVIIa has been observed, including a number of case reports in thrombocytopenia 9,10 and trauma. 11 Recently, an effect of rFVIIa was documented in a randomized placebo-controlled study in patients with a normal coagulation system undergoing retropubic prostatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…5 It has proven to be quite safe and effective in this setting. A growing number of publications document the off-label use of rFVIIa in managing bleeding in a variety of clinical settings, including platelet function disorders, 6,7 thrombocytopenia, 8 liver failure 9 and liver transplantation, 10 post-surgical 11 and following trauma. 12 It is difficult to evaluate the overall clinical efficacy and safety of rFVIIa in non-hemophiliac bleeding because the reports on its use have largely been single cases or small, uncontrolled series.…”
mentioning
confidence: 99%
“…8,21,22 The use of rFVIIa could reduce the requirement for platelet concentrates in these patients, or potentially be an effective substitute for transfusion of platelets in those patients who are refractory.…”
mentioning
confidence: 99%